Multi-Level Barriers to Prison Mental Health and Physical Health Care for Individuals With Mental Illnesses - Canada, Kelli; Barrenger, Stacey; Bohrman, Casey; Banks, Anthony; Peketi, Punita (Frontiers in Psychiatry, 2022)
Objectives: People with mental illnesses are overrepresented in the U.S. prison population. It is well established that incarceration for this population poses physical and mental health risks including greater likelihood of victimization and suicide compared to the general prison population. Yet, research is less clear about how staff and services shape these prison experiences. The aim of this study was to examine how people with mental illnesses experience incarceration through interactions with correctional officers and treatment staff and their use of physical and mental health care services. Methods: This project utilized a non-experimental design and qualitative research approach to address the research aims. Adults with mental illnesses who were formerly incarcerated were recruited from three different sites in the Midwest and East Coast. Participants completed an in-depth interview and brief survey on health histories. Data were analyzed using descriptive statistics and the framework method for qualitative analysis. Results: Participants (n = 43) identified challenges to utilizing health and mental health care including perceived access and quality of mental health, medical, or substance use treatments obtained during prison as well as participant’s willingness to engage in services. Access to health care was marked by cumbersome procedures required for service use requests and inadequate staffing. Participants reported mixed experiences with medical and mental health staff ranging from experiencing kindness to feeling staff did not believe them. Participants perceived most correctional officers as exhibiting professionalism while some enacted stigma and created additional stressors. Conclusion: Interactions with correctional staff and health care services have the potential to buffer the stressors and risks inherent in prisons for people with mental illnesses. Perceptions from participants suggest both individual- and systems-level opportunities for intervention to better support people with mental illnesses in prison.